2007
DOI: 10.1002/ijc.23203
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of human D‐glucuronyl C5‐epimerase in breast cancer

Abstract: D-glucuronyl C5-epimerase (GLCE) is one of the key enzymes in proteoglycan biosynthesis. However, nothing is known about expression and activity of the protein in cancer. In this study, we investigated GLCE expression in human breast cancer using multipex RT-PCR, QRT-PCR and Western-blot assays. In total, 21 patients without malignancy and 74 patients with breast tumor were investigated. The obtained data showed that in 82-84% of human breast tumors there is either downregulation or loss of Dglucuronyl C5-epim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…D-glucuronyl C5 epimerase, acting exclusively on heparin and heparan sulfate, was found to be decreased in breast cancer [18]. On the other hand, dermatan sulfate epimerase (DSE), according to our and other studies [12], was increased.…”
Section: Discussionmentioning
confidence: 66%
“…D-glucuronyl C5 epimerase, acting exclusively on heparin and heparan sulfate, was found to be decreased in breast cancer [18]. On the other hand, dermatan sulfate epimerase (DSE), according to our and other studies [12], was increased.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study has shown a significant reduction of D-glucuronyl C5-epimerase expression in human breast cancer. (139) Since this enzyme is normally expressed in most human tissues, detection of this change may be useful as a diagnostic and/or prognostic marker in cancer.…”
Section: Epimerizationmentioning
confidence: 99%
“…Potential tumor-suppressor function is shown for EXT1, NDST4, GLCE, and SULF1 genes and changes of their expression were detected in different human tumors: EXT1 is epigenetically inactivated in leukemia and non-melanoma skin human primary tumors and cell lines (16) and mutationally inactivated in solid osteochondromas (17), but EXT1 expression is associated with bad prognosis in multiple myeloma cells (18); NDST4 is a novel candidate tumor-suppressor gene, and the loss of its function might be involved in colorectal cancer progression (19); GLCE is down-regulated in both breast primary tumors and cell lines (20, 21) and lung cancer cell lines (22), although GLCE up-regulation correlates with aggressive disease in prostate cancer (23, 24); SULF1 is epigenetically silenced in ovarian cancer cell lines and primary tumors (25); in contrast to the tumor-suppressor effect of SULF1, SULF2 expression promotes hepatocellular carcinoma cell growth in vitro and in vivo (26); SULF2 is up-regulated in NSCLC and other cancers and implicated as a driver of carcinogenesis in NSCLC, pancreatic cancer, and hepatocellular carcinoma (27); enhanced heparanase-1 expression correlates with poor prognosis in most of the cancers in which it has been examined, and over-expression and knockout studies clearly implicate the heparanase as a master regulator of cancer progression and metastasis (28, 29). All the results support an involvement of HS-metabolic enzymes in carcinogenesis and show complex changes of their expression levels in tumors.…”
Section: Introductionmentioning
confidence: 99%